Cardiorespiratory fitness and physical strain during prosthetic rehabilitation after lower limb amputation. (August 2019) - Wezenberg, Daphne; Dekker, Rienk; van Dijk, Frank; Faber, Willemijn; van der Woude, Lucas; Houdijk, Han
Background: Sufficient cardiorespiratory fitness has been regarded a prerequisite for prosthetic walking. In order to improve cardiorespiratory fitness, adequate strain ought to be placed on the system during training. Objectives: To determine cardiorespiratory fitness at the start and end of inpatient rehabilitation after lower limb amputation and determine the physical strain experienced during conventional prosthetic rehabilitation. Study design: Multicenter prospective cohort study. Methods: Cardiorespiratory fitness was assessed using a peak one-legged cycle exercise test. Physical strain was assessed during a minimum of three full rehabilitation days using heart rate recordings. Physical strain was expressed in the time per day that heart rate exceeded 40% of heart rate reserve. Results: At the start of rehabilitation, peak aerobic capacity was on average 16.9 (SD, 6.5) mL/kg/min ( n  = 33). Overall, peak aerobic capacity did not improve over the course of rehabilitation ( n  = 23, p  = 0.464). Fifty percent of the patients experienced a physical strain level that satisfies minimum criteria for maintaining cardiorespiratory fitness (>40% heart rate reserve for 30 min/day). Conclusion: Cardiorespiratory fitness was low and did not increase during conventional prosthetic rehabilitation. On average, the physical strain during rehabilitation was insufficient to elicit potential improvements in aerobic capacity. Results stress the need for dedicated physical training modules at the individual level. Clinical relevance: This study shows that clinicians ought to be aware of the relatively low cardiorespiratory fitness of people who have undergone lower limb amputation and that improvements during rehabilitation are not always obtained. Results stress the need for physical training modules in which intensity is imposed at the individual level.